Educational policies in pandemic at valdizana dental school – Huanuco: challenges and opportunities - Maccha-Valle, Nelly F. (2022)
This essay describes experience in Dental School of National University Hermilio Valdizan in context of COVID-19 pandemic declared from March to present. Restrictive measures in higher education that were taken to face the pandemic, greatly affected pre-clinical clinical practices of Dentistry students, definitely clinical practices in real conditions are essential so that students can acquire the skills they need requires professional health careers. Dental schools around the world worked hard to continue education under this pandemic environment. In the case of dental schools of the public sector in Peru, they had to face many challenges because only some public Universities had dental simulators, however, in the case of UNHEVAL dental school, this challenge was overcome for to the teamwork of university authorities and dental school authorities who dedicated themselves to developing, modifying or implementing educational policies in such a way that quality education can continue to be provided and at the same time avoid risks regarding the contagion and spread of coronavirus.